KETIDAKADILAN GENDER DALAM FILM DANGAL KARYA AAMIR KHAN DITINJAU DALAM PANDANGAN ISLAM - Leni Andariati (PSGA LP2M IAIN Pontianak, 2021)
Dangal film released on December 23, 2016 contains about gender injustice that occurred in the village of Balali, Haryana, the northern state of India. The discussion will focus on finding out how gender inequality is found in the film Gangal?, annd how does Islam see that?. This study uses a qualitative approach with descriptive nature. In addition, researchers conducted a study of the Dangal film produced by Aamir Khan. This study found that there were several scenes that showed gender inequality in the film, namely the occurrence of marginalization, subordination, stereotyping, physical and psychological violence, while also showing the existence of gender emancipation. Such a thing when viewed in the eyes of Islam then Islam itself has confirmed that all creatures are created equal, the only difference being piety. Thus Islam strongly rejects all forms of gender injustice.